miR-277 regulates the phase of circadian activity-rest rhythm in Drosophila melanogaster - Anna, Geo; John, Maria; Kannan, Nisha N. (Frontiers in Physiology, 2023)
Circadian clocks temporally organize behaviour and physiology of organisms with a rhythmicity of about 24 hours (h). In Drosophila, the circadian clock is composed of mainly four clock genes: period (per), timeless (tim), Clock (Clk) and cycle (cyc) which constitutes the transcription-translation feedback loop. The circadian clock is further regulated via post-transcriptional and post-translational mechanisms among which microRNAs (miRNAs) are well known post-transcriptional regulatory molecules. Here, we identified and characterized the role of miRNA-277 (miR-277) expressed in the clock neurons in regulating the circadian rhythm. Down regulation of miR-277 in the pacemaker neurons expressing circadian neuropeptide, pigment dispersing factor (PDF) advanced the phase of the morning activity peak under 12h light: 12h dark cycles (LD) at lower light intensities and these flies exhibited less robust rhythms compared to the controls under constant darkness. In addition, downregulation of miR-277 in the PDF expressing neurons abolished the Clk gene transcript oscillation under LD. Our study points to the potential role of miR-277 in finetuning the Clk expression and in maintaining the phase of the circadian rhythm in Drosophila.